2015
DOI: 10.1155/2015/728127
|View full text |Cite
|
Sign up to set email alerts
|

Flow Mediated Dilatation Is Reduced with the Progressive Stages of Glomerular Filtration Rate and Albuminuria in Type 2 Diabetic Patients without Coronary Heart Disease

Abstract: We aimed to clarify the usefulness of measuring the flow mediated dilatation (FMD) in patients with type 2 diabetes mellitus without and with coronary heart disease (CHD). The FMD was measured in 480 patients with type 2 diabetes and in 240 nondiabetic subjects. The FMD was significantly lower in the subjects with CHD (n = 145, 5.4 ± 3.2%) than in those without CHD (n = 95, 6.9 ± 3.5%) among the nondiabetic subjects. The FMD was also lower in the subjects both with CHD (n = 161, 5.6 ± 2.8%) and without CHD (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…This involvement pattern suggests that shear stress–related vascular‐protection mechanisms may not be working properly or may be defective in DM. Reports indicating impaired flow‐mediated dilatation in diabetic patients also support this thought . To this end, the protective effect of shear stress on the vessel wall may well be stimulated predominantly by peak shear stress episodes induced by peak hyperemic flow velocities rather than by baseline shear stress.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This involvement pattern suggests that shear stress–related vascular‐protection mechanisms may not be working properly or may be defective in DM. Reports indicating impaired flow‐mediated dilatation in diabetic patients also support this thought . To this end, the protective effect of shear stress on the vessel wall may well be stimulated predominantly by peak shear stress episodes induced by peak hyperemic flow velocities rather than by baseline shear stress.…”
Section: Discussionmentioning
confidence: 85%
“…Reports indicating impaired flow-mediated dilatation in diabetic patients also support this thought. [32][33][34] To this end, the protective effect of shear stress on the vessel wall may well be stimulated predominantly by peak shear stress episodes induced by peak hyperemic flow velocities rather than by baseline shear stress. Accordingly, physical activity covering only %2% of daily routine is known to be enough to generate substantial functional and structural vascular improvements.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic search resulted in the inclusion of 193 from a total of 4641 potential articles (Figure ). From the 193 studies included in the analyses, vascular reactivity was assessed in a total of 26570 patients that were considered healthy (n = 7226), overweight (n = 7605), or those with obesity (n = 1758) or that were diagnosed with metabolic sy...…”
Section: Resultsmentioning
confidence: 99%
“…FMD is known to reflect the vasodilation of medium‐sized conduit arteries caused by endothelium‐derived NO. Two cross‐sectional studies among Japanese T2DM patients have reported associations between decreased FMD and albuminuria . In Maastricht study, a T2DM‐enriched population‐based cohort study in Netherlands, endothelial function was measured by different methods, including heat‐induced skin hyperemic response using LDF, flicker light‐induced retinal arteriolar dilation using dynamic vessel analyzer, and skin capillaroscopy .…”
Section: Discussionmentioning
confidence: 99%
“…patients have reported associations between decreased FMD and albuminuria. 16,17 In Maastricht study, a T2DM-enriched populationbased cohort study in Netherlands, endothelial function was measured by different methods, including heat-induced skin hyperemic response using LDF, flicker light-induced retinal arteriolar dilation using dynamic vessel analyzer, and skin capillaroscopy. 18,19 The crosssectional associations between endothelial function and albuminuria have been observed using different methods.…”
Section: Discussionmentioning
confidence: 99%